2016
DOI: 10.1037/hea0000361
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of an online mother-daughter body image and well-being intervention.

Abstract: Poor body image is a public health issue. Mothers are a key influence on adolescent girls' body image. This study evaluated an accessible, scalable, low-intensity internet-based intervention delivered to mothers (Dove Self Esteem Project Website for Parents) on mothers' and their adolescent daughters' body image and psychosocial well-being. Method: British mother-daughter dyads (N ϭ 235) participated in a cluster randomized controlled trial (assessment-only control; mothers viewed the website without structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…The BES-A would be an appropriate primary outcome measure for a future RCT. The BES-A is frequently used in adolescent body image research because it is reliable, has normative data, and has good face validity among adolescents (eg, a study by Diedrichs et al [38]); it provides a general measure of satisfaction with appearance and is not condition specific, making it appropriate for those with any appearance-affecting condition. In this study, YP fed back that it was quick and easy to complete, and results indicated it is sensitive to change among those completing the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…The BES-A would be an appropriate primary outcome measure for a future RCT. The BES-A is frequently used in adolescent body image research because it is reliable, has normative data, and has good face validity among adolescents (eg, a study by Diedrichs et al [38]); it provides a general measure of satisfaction with appearance and is not condition specific, making it appropriate for those with any appearance-affecting condition. In this study, YP fed back that it was quick and easy to complete, and results indicated it is sensitive to change among those completing the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a recent study by Diedrichs et al (2016) found that tailoring intervention content to suit the preferences of individual mothers was effective in improving mothers' engagement with the intervention and maternal psychosocial outcomes, but had little impact on daughters' outcomes. Consequently, during the intervention development and implementation phase of child body image interventions delivered to parents, daughters' preferences are likely to require attention.…”
Section: Discussionmentioning
confidence: 99%
“…Dyads were recruited for a larger study evaluating an online intervention for mothers that was designed to improve their adolescent daughters' body image (Diedrichs et al, 2016). Of the total sample recruited, 190 dyads reported their preferences for body image intervention content and their data is reported here.…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…70 There is also evidence that brief online interventions delivered to parents can improve both their own and their children's body image and psychological wellbeing. 71 At a wider level, research has shown that increasing appearance diversity in advertising and media is beneficial for body image. 72,73 Social policy initiatives, such as voluntary codes of conduct to increase acceptance of diversity in appearance and promote positive body image in advertising and media have been developed in Australia, Canada and the UK.…”
Section: Education and Trainingmentioning
confidence: 99%